Pyrethroid insecticides maintain repellent effect on knock-down resistant populations of Aedes aegypti mosquitoes. - Natalie M Bowman (PLoS ONE, 2018)
Pyrethroid-treated clothing is commonly worn for protection against mosquitoes; pyrethroids are both insecticides and repellents. Pyrethroid resistance has become increasingly common in Aedes aegypti, the vector of dengue, Zika, and other arboviruses, but it is not clear whether resistance is associated with reductions in repellency. In order to determine whether long-lasting permethrin impregnated (LLPI) clothing is protective, we used Aedes aegypti from New Orleans, LA (pyrethroid-sensitive) and San Juan, PR (resistant) to measure both lethality and repellency. PCR and Sanger sequencing were used to confirm resistance status by detecting mutations in the kdr gene at positions 1016 and 1534. Arm-in-cage trials of 100 Aedes aegypti females from both populations were performed for 10 minutes to bare arm or an arm clothed in untreated military camouflage or military camouflage impregnated with deltamethrin, permethrin, or etofenprox. Trials were repeated 4-5 times on different days. Number of landings, number of blood meals, and immediate and 24-hour mortality were recorded. Mortality was extremely low in all trials. Compared to untreated cloth, mosquitoes demonstrated a trend towards a 2%-63% reduction in landings and a statistically significant 78-100% reduction in blood feeding on pyrethroid-treated cloth for most insecticides. Effects were observed in both pyrethroid-sensitive and pyrethroid-resistant mosquito populations. Our data show that kdr mutations are associated with pyrethroid resistance but are likely not the only contributors. Pyrethroids appear to maintain repellent effect against resistant mosquitoes. This finding suggests that even in places where pyrethroid resistance is widespread, permethrin still has a role for use as a repellent on clothing to protect against mosquito bites.